Eksistensi Republik Maluku Selatan sebagai Subjek Hukum Internasional: Antara Legitimasi dan Legalitas - Lindra Darnela (Universitas Muhammadiyah Purwokerto, 2022)
The Republic of South Maluku (RMS) at the beginning of its birth in the 1950s gained a place in international law as a group that has the right of self-determination by proclaiming itself as an independent Republic. Their presence became more apparent when those who were former KNIL members chose to temporarily move to the Netherlands and freely raised the RMS flag in the country. This paper discusses the existence of the Republic of South Maluku in international law recently, based on the perspective of legitimacy and legalization. This study used the interview method with several RMS figures, RMS descendants and some researchers on RMS. This research found that RMS currently no longer has legitimacy either in the Netherlands or in the Moluccas. This is supported by the lack of movement and support for the current RMS in Maluku and the existence of the RMS in the Netherlands at present only as their negotiations against the Dutch government as a minority group. Besides, in international law RMS is not a legal subject because it is no longer in the Belligerent category and is recognized by countries.Keywords: Republic of South Maluku (RMS), legitimacy, legality, international law